2004
DOI: 10.1038/sj.cdd.4401438
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of TNF-α-induced ceramide formation in human glioma cells:P53-mediated oxidant stress-dependent and -independent pathways

Abstract: The present study was designed to examine the roles of p53, reactive oxygen species (ROS), and ceramide, and to determine their mutual relationships during tumor necrosis factor (TNF)-a-induced apoptosis of human glioma cells. In cells possessing wild-type p53, TNF-a stimulated ceramide formation via the activation of both neutral and acid sphingomyelinases (SMases), accompanied by superoxide anion (O 2 ÀK ) production, and induced mitochondrial depolarization and cytochrome c release, whereas p53-deficient ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 59 publications
(92 reference statements)
3
48
3
1
Order By: Relevance
“…Construction of the destination vector, pDEST-CL-SI-MSCVpuro, for retroviral expression of shRNA, pCL-SI-MSCVpuro-ErbB2R-shRNA, -HPV16E6-shRNA, -p53-shRNA and -E6AP-shRNA was carried out by a previously described method (Sawada et al, 2004). The shRNA targeted sequences were as follows: HPV16E6: GTATGGAACAACATTAGAA, E6AP: 5 0 -GAAATCTAGT GAATGATGA-3 0 , p53 (18) and ErbB2 (Yang et al, 2004) as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of the destination vector, pDEST-CL-SI-MSCVpuro, for retroviral expression of shRNA, pCL-SI-MSCVpuro-ErbB2R-shRNA, -HPV16E6-shRNA, -p53-shRNA and -E6AP-shRNA was carried out by a previously described method (Sawada et al, 2004). The shRNA targeted sequences were as follows: HPV16E6: GTATGGAACAACATTAGAA, E6AP: 5 0 -GAAATCTAGT GAATGATGA-3 0 , p53 (18) and ErbB2 (Yang et al, 2004) as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they found that, indeed, TNF-α caused a rapid increase of superoxide free radical within 2 minutes, but the effect was not sustained and dissipated after 60 minutes [24,25]. TNF-α can stimulate ceramide formation via the activation of both neutral and acid SMases, accompanied by ROS such as superoxide anion production [26]. TNF-α initiates the pathway through TNFR1 (55-kDa receptor) leading to phospholipase A2 activation, generation of arachidonic acid, and subsequent activation of SMase [27].…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%
“…Coding sequences of the oncogenic mutant K-ras (Kras-G12V) and an activated form of Akt with a src myristoylation sequence (myrAkt) (Kohn et al, 1996) were first recombined into pDONR201 or pDONR221 (Invitrogen, Carlsbad, CA, USA) by performing the BP reaction according to the manufacturer's instruction, and were then recombined into the destination vector, pDEST-CMSCVpuro, by performing the LR reaction (Invitrogen, Carlsbad, CA, USA) to generate pCMSCVpuro-K-ras* and pCMSCVpuro-myr-Akt. To generate a retrovirus vector expressing PTEN-specific shRNA, the annealed oligos (5 0 gatccccGACATTATGACACCGCC AAttcaagagaTTGGCGGTGTCATAATGTCtttttggaaa3 0 and 5 0 agcttttccaaaaaGACATTATGACACCGCCAAtctcttgaaTT GGCGGTGTCATAATGTCggg3 0 ) were replaced with the stuffer of pENTR221-H1R-stuffer (Sawada et al, 2004). The shRNA expression cassette was recombined into pDEST-CL-SI-MSCVpuro (previously called pSI-CMSCVpuro-DEST) (Sawada et al, 2004), by performing the LR reaction (Invitrogen) according to the manufacturer's instruction to generate pCL-SI-MSCVpuro-H1R-PTENRi8.…”
Section: Vector Construction and Retroviral Infectionmentioning
confidence: 99%
“…To generate a retrovirus vector expressing PTEN-specific shRNA, the annealed oligos (5 0 gatccccGACATTATGACACCGCC AAttcaagagaTTGGCGGTGTCATAATGTCtttttggaaa3 0 and 5 0 agcttttccaaaaaGACATTATGACACCGCCAAtctcttgaaTT GGCGGTGTCATAATGTCggg3 0 ) were replaced with the stuffer of pENTR221-H1R-stuffer (Sawada et al, 2004). The shRNA expression cassette was recombined into pDEST-CL-SI-MSCVpuro (previously called pSI-CMSCVpuro-DEST) (Sawada et al, 2004), by performing the LR reaction (Invitrogen) according to the manufacturer's instruction to generate pCL-SI-MSCVpuro-H1R-PTENRi8. The backbone vector, pCL-SI-MSCVpuro-H1R, was used as a control (Sawada et al, 2004).…”
Section: Vector Construction and Retroviral Infectionmentioning
confidence: 99%
See 1 more Smart Citation